Comparison of Art Education Modes Between Chinese and Western Museums: Taking the Difference Between “Utensil-Oriented” and “Audience-Oriented” as an Example (Journal of humanities and social sciences exploratio, 2026)
This paper makes a systematic comparison of the structural differences between Chinese and Western Museum art education models through the lens of the two core concepts of "utensil orientation" and "audience orientation". The study found that the education model represented by China focused on the authoritative interpretation and systematic knowledge teaching of art noumenon, reflecting the profound tradition of "utensil orientation"; However, the education model, which is typical of the contemporary practice in Europe and America, emphasizes the audience experience as the center, pays attention to interactive participation and personal meaning construction, showing a distinctive "audience oriented" feature. The distinction stems from the different cultural philosophy, knowledge tradition and Museum positioning of both sides. The paper discusses the advantages and disadvantages of the two modes from three aspects: Historical Tracing, dimensional comparison and case analysis. Finally, the ideal path for the future is not a simple choice, but to find a way to creatively integrate professional depth and public experience on the basis of a full understanding of the local cultural context, so as to provide a theoretical reference for the innovative development of art education in Chinese museums.
Keywords: Museum; Art education; Educational model; Utensils; Audience orientation